2021
DOI: 10.1121/10.0005131
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the acoustic environment during COVID-19 lockdown in Argentina

Abstract: The COVID-19 pandemic has significantly modified the behavior of societies. The application of isolation measures during the crisis resulted in changes in the acoustic environment. The aim of this work was to characterize the perception of the acoustic environment during the COVID-19 lockdown of people residing in Argentina in 2020. A descriptive cross-sectional correlational study was carried out. A virtual survey was conducted from April 14 to 26, 2020, and was answered mainly by social network users. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Spending the lockdown in houses with poor indoor environmental conditions (including acoustic discomfort) was found to be associated with a higher risk of moderate–severe and severe depressive symptoms [27] . In indoor spaces, natural sounds coming from the outdoor environment and unmasked by the drop in anthropogenic noise in cities during the lockdown [28] , [29] , [30] might provide improved cognitive performance and stress recovery [31] , despites findings of restorative effects of natural sounds being still inconclusive [32] . Listening to music can be a coping strategy for dealing with stress, can involve emotion regulation and provide psychotherapeutic effects [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Spending the lockdown in houses with poor indoor environmental conditions (including acoustic discomfort) was found to be associated with a higher risk of moderate–severe and severe depressive symptoms [27] . In indoor spaces, natural sounds coming from the outdoor environment and unmasked by the drop in anthropogenic noise in cities during the lockdown [28] , [29] , [30] might provide improved cognitive performance and stress recovery [31] , despites findings of restorative effects of natural sounds being still inconclusive [32] . Listening to music can be a coping strategy for dealing with stress, can involve emotion regulation and provide psychotherapeutic effects [33] .…”
Section: Introductionmentioning
confidence: 99%
“…While noise level reductions due to the lockdown and social distancing policies imposed to counter the spread of the virus were generally acknowledged, what happened in terms of experience and perception of the sound environment as per the soundscape concept [13] was less clear. Maggi et al [14] performed an online survey on the soundscape during the lockdown in Argentina and reported that, due to the decrease in mechanical sounds and increase in natural sounds, participants were more frequently conveying feelings of tranquility and happiness. Likewise, Bartalucci et al [15] in another online survey conducted in Italy during different stages of COVID-19-related lockdowns reported an overall reduction in terms of noise annoyance that was likely induced by the limitation of traffic flows and human activities, which in turn led to improved soundscape assessments.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Tong and Kang ( 2021 ) examined the association between noise complaints and urban morphology features, e.g., roads, land uses, and buildings in New York, and found an uptick in complaints in denser areas with wider roads. In South America, Maggi et al ( 2021 ) conducted a survey with 1371 participants in Argentina and examined the sound environment against the COVID-19 backdrop, and found that mechanical noise, particularly in larger cities, dominated before the pandemic while natural sounds and tranquility feelings showed an increase during the lockdown.…”
Section: Overview Of the Literaturementioning
confidence: 99%